Social Harmony in Wonomulyo, Polewali Mandar Regency - Rahman, Abdul (Formosa Journal of Sustainable Research, 2024)
This research aims to determine harmony in Wonomulyo. This research is a qualitative research. Data was obtained through observation and in-depth interviews with informants who had lived for at least 5 years. Validation of data is carried out through member check. The research results show that the integration pattern that is realized is mutual cooperation and cooperation. The people in Wonomulyo, even though they are from different ethnicities, respect each other. Harmony is created through economic and cultural activities. Javanese people display cultural attractions at events commemorating religious holidays and Indonesian independence day events